Neuroprotective Effect of Coumarin Nasal Formulation: Kindling Model Assessment of Epilepsy - Muke, Suraj; Kaikini, Aakruti; Peshattiwar, Vaibhavi; Bagle, Sneha; Dighe, Vikas; Sathaye, Sadhana (Frontiers in Pharmacology, 2018)
Epilepsy is a brain disorder characterized by sudden recurrent seizures. Considering the fact that epileptogenesis is a process that affects the quality of life, our goal is to delay the process of epileptogenesis and to increase the latency of epileptic attacks, offering better quality of life to patients. Traditional system of medicines has a promise in some of the medicines, which have been used for the treatment of epilepsy. One such medicinal plant is Eclipta Alba (EA). According to Ayurvedic philosophy, the juice of leaves of EA is pounded with garlic and pepper for the treatment of epilepsy. Taking clue from the Ayurvedic system of medicines; we formulated coumarin fraction of EA; namely Coumarin nasal formulation (CNF) for its nasal delivery. CNF was analyzed by using High performance liquid chromatography (HPLC) and ultraviolet absorption spectroscopy for its drug content determination. In vitro drug release studies were performed in simulated nasal electrolyte solution (SNES) maintaining constant pH of 5.5 at 37 °C. Irritation by CNF was evaluated using Hen egg test-chorioallantoic membrane (HET-CAM) assay. Formulation was found to be non–irritant in HET-CAM assay. CNF was further assessed in vivo by measuring the progress and attainment of pentylenetetrazole (PTZ) kindling in mice. Neuronal changes were assessed by hematoxylin and eosin (H&E) and Nissl staining technique. Glial fibrillary acidic protein (GFAP) a neuroinflammatory marker and tumor necrosis factor alpha (TNF-α) an inflammatory marker were also measured. CNF (10 mg/kg, nasal route) when given as a pretreatment lowered seizure score and delayed the progression of seizure similar to Diazepam. CNF decreased the PTZ induced oxidative damage, TNF-α as well as GFAP levels in the mid brain tissue particularly in hippocampus region. The results suggest that CNF may be a promising therapeutic approach to offer protection from sudden recurrent seizures alone or in combination with current drugs in management of epilepsy.